Analisis Komparatif Kedudukan Saldo E-Wallet sebagai Objek Warisan dalam Perspektif Hukum Islam dan Hukum Perdata di Indonesia - Vindira Edka Juniar; Mulida Hayati; Nuraliah Ali; Thea Farina (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The balance of e-wallets as digital assets raises legal problems when the owner dies and has not been explicitly regulated in the inheritance system. This normative research analyzes the position of e-wallet balances as inherited assets according to Islamic law and Indonesian civil law through a regulatory and conceptual approach. The results of the study show that e-wallet balances are recognized as an object of inheritance based on Article 171 letter (d) of the KHI, Fatwa DSN-MUI Number 116/DSN-MUI/IX/2017, as well as Articles 499 and 511 paragraph (3) of the Civil Code, with the mechanism of division of faraid in Islamic law and ab intestato in civil law, so special arrangements are needed to ensure legal certainty and protection of heirs' rights.